In vitro Micropropagation of Bacopa monnieri (L.) Penn. - An Important Medicinal Plant (Plant Tissue Culture and Biotechnology, 2020)
Investigation on in vitro multiple shoot regeneration in Bacopa monnieri (L.) Penn. using leaf and nodal explants was carried out on MS containing various concentrations and combinations of BAP, Kn, NAA and 2,4-D. Of the two explants, leaf showed the best response towards shoot regeneration and subsequent plant development on MS with 1.0 mg/l BAP and 0.25 mg/l Kn. In this combination, the mean number of shoots/explant was 10.6 ± 0.11 in leaf and 9.6 ± 0.29 in nodal explants. Maximum shoot length was recorded as 12.6 ± 0.21 and 11.20 ± 0.30 from leaf and nodal explants after six weeks of culture, respectively. Half strength of MS supplemented with 0.25 mg/l IBA was found to be the best medium for root formation. The in vitro regenerated plantlets were successfully transplanted in soil after acclimatization.Plant Tissue Cult. & Biotech. 30(1): 57-63, 2020 (June)